OSTEOPOROZ VE SOL KALP TUTULUMU OLAN NOONAN SENDROMU OLGUSU - DEMİR, Ferunda; KURTOĞLU, Selim; ATABEK, M. Emre; KESKİN, Mehmet; NARİN, Nazmi (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Noonan syndrome one of the non-chromosomal syndromes is characterized by short stature webbed neck, dysmorphic faces, cardiac anomalies, the skeletal and lymphatic system abnormalities and mild degrees of mental retardation. The major cardiovascular defects are valvular pulmoner stenosis, hypertrophic cardiomyopathy and atrial septal defect. However left-sided cardiac lesions including aortic and mitral valve has been rarely published. Growth retardation is one of the major application reasons in Noonan syndrome in childhood. The cause of the growth retardation is unclear. This report describes a 15 year-old girl, applying with complaint of strabismus and diagnosed as Noonan syndrome according to the fenotypic features. Un expectedly the patients has left-sided cardiac lesions including bicuspid aortic valve, aortic and mitral valve deficiency and osteoporpsis. The etiology of osteoporosis seems likely unclear. We recommend emphasizing attentive echocardiographic evaluation and appreciation of osteoporosis in Noonan syndrome.